Petrogenesis and rare earth element economic potential of Pilot Knob, a Pliocene (?) alkaline intrusive complex in the Togwotee Pass region, northwestern Wyoming (U.S.A) - Dodd, Zachary Caleb (Kansas State University, 2015)
Previous K-Ar dating and petrography (Obradovich, 1978) have identified Pilot Knob as an ~3.4 (±0.06) Ma alkaline intrusive body. Bulk rock geochemistry obtained via XRF from four samples of Pilot Knob verifies the transitionally alkaline composition of the body, and new REE data also show enriched La, Ce, and Nd concentrations, consistent with rare earth element (REE) enrichment. Given the increased demand for REEs over the past ~30 years and China accounting for > 90% of global REE production (Kynicky, et al. 2012), it is important to evaluate new domestic REE sources. This includes those associated with alkaline intrusive complexes, because they are demonstrated to host high REE concentrations (Verplanck and Van Gosen, 2011). Such alkaline igneous occurrences show complex mineralization and consist of many minerals containing substitutional REEs (Mariano and Mariano, 2012). This study evaluates the petrogenesis and mineralogy of Pilot Knob (and a secondary field site, Wildcat Hill) and determines whether the intrusive body is consistent with an economically viable REE deposit. Additionally, given its geographic location and Pliocene faulting and magmatism (e.g., predating the earliest volcanism at Yellowstone), Pilot Knob may represent one of the earliest structural manifestations of the “arrival” of the Yellowstone hotspot at its current location under the North American lithosphere or magmatism associated with lithospheric extension to the south at the Leucite Hills, WY. Inspection of satellite imagery, which has been verified with field data, shows that other intrusive igneous bodies (e.g. - Wildcat Hill) exist, along an apparent normal fault zone along strike with a major extensionally related fault zone documented ~10 km northwest of Pilot Knob. Clinopyroxene geobarometry, coupled with Nd isotope data (εNd[subscript 3.5Ma] = -21.9), indicates that Pilot Knob formed via a multi-stage development history that initiated with melting of ancient lithospheric mantle, where crystallization occurred at a variety of depths. As an alkaline intrusive complex, Pilot Knob has been identified, based on mineral and chemical compositions, as a kersantite, and has been found to contain approximately 600 ppm total light-rare earth element ore lode with ~150 ppm Nd, ~175 ppm La, and ~338 ppm Ce enrichment. Apatite was found to be the primary REE-bearing mineral via petrography and electron microprobe analyses. Based on current technology and processing methods, REE concentrations were not found to be significant enough to denote an economically viable REE ore deposit at Pilot Knob.
Keywords: Geology; Rare Earth Elements; Petrogenesis; Wyoming; Pilot Knob; Intrusive complex; Geology (0372); Geomorphology (0484)